Kearifan lokal masyarakat menyikapi konservasi lahan pesisir di Desa Cemara Labat Kabupaten Kapuas - Muhammad Tito; Yetrie Ludang; Suandi Sidauruk; Revi Sunaryati (Unri Conference Series: Community Engagement, 2022)
Utilization of coastal land in the community of Cemara Labat Village has been passed down from generation to generation. The people of Cemara Labat Village still maintain the tradition of coastal land management, such as planting certain types of mangroves, prohibiting cutting down mangrove forests and hunting animals which are regulated in unwritten customary law or local wisdom. Utilization of coastal area resources by humans from time to time continues to increase. The intensity of exploiting the potential of coastal areas resources often does not pay attention to the carrying capacity and principles of optimal and sustainable use of natural resources. Therefore, the mangrove forest ecosystem in Cemara Labat Village needs to be preserved both ecologically and biologically with an awareness approach to local wisdom. The data collection which used in this research was interview method, observation method, and survey. The results showed that Avicennia marina species had a very high dominance (80%) in the mangrove forest area of Cemara Labat Village, especially in the mangrove forest area, was bird species (Aves), while the level of community participation in mangrove forest conservation was moderate (76%). The strategy of developing community local wisdom on coastal land conservation in Cemara Labat village is in the Strengths-Opportunities or SO strategy, which is quadrant I which means Growth (6.40) or experiencing growth